The Effectiveness Of Natoni In Timor Dawan Customs : English - Yanti Boimau Yanti; Kadek Ayu Cintya Adelia Kadek (Kawalu: Journal of Local Culture, 2019)
The number of tribes that inhabit the Indonesian nation differs in ethnicity, religion, race and even language so that people who live in these differences have different cultures. Culture is a way of life that develops and is shared by a group of people and is passed down from generation to generation. Culture that is maintained and carried out continuously or repeatedly can be called a tradition. One of the cultures in the Timorese society that has become a tradition and is still being preserved today is "Natoni." In natoni, a group of people join in it, one person as a speaker or speaker (Atonis) and another group of people as a companion (Na'heen). This study aims to find out how the practice of ritual communication and effectiveness carried out through natoni by the Timorese (Dawan) tribe in East Nusa Tenggara Province. The research approach used is qualitative research. Data was collected through in-depth interviews and observations. In Timorese customs or Dawan Natoni customs, it is a form of traditional performing arts or speech rituals. In natoni, a group of people who perform this ritual, the clothes used are beti, namely traditional woven cloth on the waist and pilu or cloth tied around the head as the traditional clothing of the Dawan tribe. As a culture for the Dawan tribe, the findings of natoni are inherited from the ancestors who have used it for a long time. The Dawan tribe is known as a tribe with a high sense of politeness, making natoni as their identity. This is because natoni is a deep respect. Accordingly, natoni is understood as a welcome with a sincere heart.